Public led online trials and participatory action research: Why do we need them? - Price, A (European Society for Person Centered Healthcare, 2016)
Aim: The aim of this paper is to propose a participatory action research network where the public are equipped with the tools to become informed and responsible shared research decision-makers who help prioritize, initiate, design, organize and participate in health research through online randomized controlled trials about health and wellbeing. Concept Summary: Public involvement in clinical trials tends to focus on patient values and experience rather than increasing research literacy or fostering active collaboration and informed shared decision-making amongst citizens. Although literature searches reveal bespoke platforms and pockets of participant collaboration in online trials there are no known international research initiatives exploring this perspective through participatory action research. The potential and the limitations of pragmatic "Does it Work?" clinical trials for engaging citizen collaborators is discussed in addition to the capacity of public led online clinical trials to increase research literacy and participant satisfaction.